Making the Internet a safer place: students' perceptions about Internet security threats - Vrana, Radovan (Array, 2012)
Today's generations of students are among most frequent users of the Internet. During use of the Internet, students' computers are exposed to different types of security threats. To find out more about students' perceptions of this topic, a research at the FHSS in Zagreb was carried out. Results of the research show that respondents successfully recognized most common security threats, however they do not employ all the necessary basic protective measures available to them. They also feel that they are not fully capable of protecting their computers on the Internet, so they need more education in this area.